2016
DOI: 10.14740/jocmr2702w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Hydroxyethyl Starch (Voluven) Solution With Normal Saline in Hemorrhagic Shock Treatment in Trauma

Abstract: BackgroundAppropriate fluid therapy affects morbidity and mortality rates. A conclusion is yet to be reached on the role of crystalloids and colloids in immediate fluid therapy. This study was done to determine the suitable solution in immediate resuscitation of patients with hemorrhagic shock caused by tissue trauma.MethodsOne hundred trauma patients with hemorrhagic shock, who underwent fluid therapy in the emergency unit, were assigned randomly to two groups of hydroxyethyl starch (Voluven) and normal salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…The prognostic survival of the traumatic shock rats was remarkably improved after fluid resuscitation using HES, which is consistent with previous studies [ 11 , 17 ]. It should be noted that in their SD rat models of traumatic hemorrhagic shock, Masoumi et al [ 18 ] discovered that HES resuscitation regulates the balance of TH1/TH2 response, inhibits NF- κ B activation, and promotes CD4+T cell apoptosis of the traumatic hemorrhagic rats, thus improving the immunosuppression, disorder, and inflammation of the rats, which is also in line with our results. In our study, the results of flow cytometry showed that the apoptosis rate of lymphocytes in LR and CON groups was significantly higher than that in sham and HES groups.…”
Section: Discussionsupporting
confidence: 91%
“…The prognostic survival of the traumatic shock rats was remarkably improved after fluid resuscitation using HES, which is consistent with previous studies [ 11 , 17 ]. It should be noted that in their SD rat models of traumatic hemorrhagic shock, Masoumi et al [ 18 ] discovered that HES resuscitation regulates the balance of TH1/TH2 response, inhibits NF- κ B activation, and promotes CD4+T cell apoptosis of the traumatic hemorrhagic rats, thus improving the immunosuppression, disorder, and inflammation of the rats, which is also in line with our results. In our study, the results of flow cytometry showed that the apoptosis rate of lymphocytes in LR and CON groups was significantly higher than that in sham and HES groups.…”
Section: Discussionsupporting
confidence: 91%
“…There are many reports on the effects of HES130 administration in patients with massive hemorrhages; HES130 has been shown to shorten the recovery time from shock [12], improve peripheral circulation and vascular permeability, improve the symptoms of edema in small intestinal mucosa [30], and decrease the concentrations of GCX fragmentation products (syndecan-1, heparanase, and hyaluronic acid) [31]. In addition, in a clinical study of HES130 treatment in trauma patients, an improvement of base excess [32] and lactic acid levels was reported. Rossaint et al reported that HES130 treatment reduced neutrophil-platelet aggregates, chemokine-induced arrest, and the transmigration of neutrophils; HES130 has also been found to have antiinflammatory effects [14].…”
Section: Discussionmentioning
confidence: 99%
“…Crystalloids by entering extravascular space may not completely replace intravascular space. Some studies have demonstrated that administration of Voluven and crystalloid fluids showed no significant difference between the two groups of the patients in the hemodynamic parameters (10, 16). Considering the importance of hemodynamic stability during SA, especially in pregnant women, and the presence of the contradictory results from earlier studies.…”
Section: Introductionmentioning
confidence: 98%